أثر الابتكار التسويقي على جودة الخدمات الصحية من وجهة نظر المرضى في مشفى الباسل بطرطوس - برهوم, أديب; سعيد, رشا (Latakia University Journal - Economic and Legal Sciences Series, 2014)
هدفت هذه الدراسة إلى التعرف على أثر الابتكار التسويقي (الابتكار على مستوى الأفراد, الابتكار على مستوى الإجراءات, الابتكار على مستوى التكنولوجيا) على جودة الخدمات الصحية بأبعادها (الاعتمادية, الملموسية, الاستجابة, الأمان, التعاطف) في مشفى الباسل بطرطوس. تم جمع البيانات الأولية للبحث من خلال استبيان تم توزيعه على عينة ملائمة من مجتمع البحث, وتم تحليل هذه البيانات من خلال برنامج الـ SPSS الإحصائي. ولاختبار فرضيات الدراسة تم استخدام تحليل الانحدار البسيط والانحدار المتعدد. ومن أهم النتائج التي تم التوصل إليها: 1- وجود تأثير معنوي لمجمل عناصر الابتكار التسويقي على إجمالي أبعاد جودة الخدمات الصحية. 2- وجود تأثير معنوي لعنصر الابتكار في الإجراءات على إجمالي أبعاد جودة الخدمات الصحية. 3- وجود تأثير معنوي لعنصر الابتكار على مستوى الأفراد على كل من الاعتمادية والملموسية, ولكن لم يكن هناك تأثير معنوي لعنصر الابتكار على مستوى الأفراد على كل من الاستجابة والأمان والتعاطف. 4- وجود تأثير معنوي لعنصر الابتكار التكنولوجي على كل من الاعتمادية والملموسية والاستجابة, ولكن لم يكن هناك تأثير معنوي لعنصر الابتكار التكنولوجي على كل من الأمان والتعاطف. This study aimed to identify the impact of the Marketing Innovation (Innovation on the individual, procedure, and technology levels) on the quality of health services dimensions (Reliability, Tangibility, Responsiveness, Security and Empathy) in the al-Bassel hospital in Tartous. Research primary Data were collected through a questionnaire was distributed to an appropriate sample of research community, the data were analyzed by the SPSS statistical program. The simple and multiple regression was used to test the research hypotheses. The main findings of the study are: 1- There is a significant impact of the total marketing innovation on the total dimensions of health services quality. 2- There is a significant impact of the innovation in procedure on the total dimensions of health services quality. 3- There is a significant impact of the innovation on the individual on the reliability and tangibility, but innovation on the individual has no significant impact on the responsiveness, security and empathy. 4- There is a significant impact of the technology innovation on the reliability, tangibility and responsiveness, but technology innovation has no significant impact on the security and empathy.